The role of the growth hormone in assisted reproductive technologies cycles - Andrey Y Romanov; Anastasiya G Syrkasheva; Nataliya V Dolgushina; Elena A Kalinina (IP Berlin A.V., 2019)
The paper analyzes the literature data on the use of the growth hormone (GH) in ovarian stimulation in assisted reproductive technologies (ART). Routine use of GH in ovarian stimulation in patients with a normal GH level does not increase pregnancy and childbirth rates in ART. Also, no benefits of using GH have been identified for patients with polycystic ovary syndrome, despite the increase in insulin and IGF-1 blood levels. The main research focus is to study the use of GH in patients with poor ovarian response. According to the meta-analysis conducted by X.-L. Li et al. (2017), GH in ovarian stimulation of poor ovarian responders increases the number of received oocytes, mature oocytes number, reduces the embryo transfer cancellation rate and does not affect the fertilization rate. The pregnancy and live birth rates are significantly higher in the group of GH use - by 1.65 (95% CI 1.23-2.22) and 1.73 (95% CI 1.25-2.40) times, respectively. Thus, it is advisable to use GH in ovarian stimulation in poor ovarian responders, since it allows to increases live birth rate in ART. However, further studies should determine the optimal GH dose and assesse it`s safety in ART programs.